Eutrophication: Causes, Consequences and Control Volume 2 - Ansari, Abid A.; Gill, Sarvajeet Singh; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2014)
Eutrophication continues to be a major global challenge, and the problem of eutrophication and availability of freshwater for human consumption is an essential ecological issue. The global demand for water resources due to increasing population, economic developments, and emerging energy development schemes has created new environmental challenges for global sustainability. Accordingly, the area of research on eutrophication has expanded considerably in recent years. Eutrophication, acidification and contamination by toxic substances are likely to pose increasing threats to freshwater resources and ecosystems. The consequences of anthropogenic-induced eutrophication of freshwaters are severe deterioration of surface waters and growing public concern, as well as new interest among the scientific community. “Eutrophication: causes, consequences & control” provides the latest information on many important aspects of the processes of natural and accelerated eutrophication in major aquatic ecosystems around the world. “Eutrophication: causes, consequences & control” offers a cutting-edge resource for researchers and students alike who are studying eutrophication in various ecosystems. It presents the latest trends and developments in the field, including: global scenarios and local threats to the dynamics of aquatic ecosystems, economics of eutrophication, eutrophication in the great lakes of the Chinese pacific drainage basin, photoautotrophic productivity in eutrophic ecosystems, eutrophication’s impacts on natural metal remediation in salt marshes, phytoplankton assemblages as an indicator of water quality in seven temperate estuarine lakes in southeast Australia, biogeochemical indicators of nutrient enrichments in wetlands – the microbial response as a sensitive indicator of wetland eutrophication, and ultraviolet radiation and bromide as limiting factors in eutrophication processes in semi-arid climate zones. Written by respected experts and featuring helpful illustrations and photographs, “Eutrophication: causes, consequences & control” provides a concise and practical update on the latest developments in eutrophication.
1. Eutrophication: Challenges and Solutions -- 2. Eutrophication: Global Scenario and Local Threat to Dynamics of Aquatic Ecosystems -- 3. Effects of Eutrophication -- 4. The Economics of Eutrophication -- 5. Eutrophication of Lakes -- 6. Lake Eutrophication and Plankton Food Webs -- 7. Environmental Impacts of Tourism on Lakes -- 8. Eutrophication in the Great Lakes of the Chinese Pacific Drainage Basin: Changes, Trends and Management -- 9. Photoautotrophic Productivity in Eutrophic Ecosystems -- 10. Seasonal and Spatial Nutrient Dynamics in Saronikos Gulf: The Impact of Sewage Effluents from Athens Sewage Treatment Plant -- 11. Eutrophication Impacts on Salt Marshes Natural Metal Remediation -- 12. Household Detergents Causing Eutrophication in Freshwater Ecosystems -- 13. Estimating Fish Production in the Itaipu Reservoir (Brazil): The Relationship between Fish Trophic Guilds, Limnology and Application of Morphoedaphic Index -- 14. Phytoplankton Assemblages as an Indicator of Water Quality in Seven Temperate Estuarine Lakes in South-East Australia -- 15. Biogeochemical Indicators of Nutrient Enrichments in Wetlands: The Microbial Response as a Sensitive Indicator of Wetland Eutrophication -- 16. Task of Mineral Nutrients in Eutrophication -- 17. Phytoremediation Systems for the Recovery of Nutrients from Eutrophic Waters -- 18. Ultra Violet Radiation and Bromide as Limiting Factors in Eutrophication Processes in Semi-Arid Climate Zones.
Keywords: Water pollution; Water quality; Aquatic ecology .; Plant ecology; Waste Water Technology / Water Pollution Control / Water Management / Aquatic Pollution; Water Quality/Water Pollution; Freshwater & Marine Ecology; Plant Ecology